EXPORT POTENTIAL OF ELVERS AND CULTURED EELS FROM INDIA - Nair, R V (Indian Journal of Fisheries, 2011)
Thie elvers of the eel Anguilla bic<^or McClelland have been collected at SHvaikundam anicut on River Tambrapami and successfully cultjired in running water iecperimental tanks at Mandapam Camp. The growth rate of cultured eds has been found to be very rapid during the first year and slower in the Kcood year. Elvers about 10 cm in length and 2 gm in weight have attained a size (^ 35 cm in length and 106 gm in weight at the uid of first year and 42 cm mad 160 gm respectively at the end of the second year. The largest eel measured 50 cm at the end of the first year. The harvesting of cultured eels at the end of the firsit year is suggested since the eels reach marketable size by then and it may be uiqsofitable to continue farming for second year in view of the slow growth and additional expenditure involved.